Samuel Pufendorf disciple of Hobbes : for a re-interpretation of modern natural law - Palladini, Fiammetta; Saunders, David; Hunter, Ian (Early modern natural law, 2020)
Fiammetta Palladini’s work is one of the most important discussions of Pufendorf to appear in the latter part of the twentieth century. It cut through the existing field of Pufendorf studies, laying bare its inherited templates and tacit assumptions. Palladini was thus able to peel back the ‘Grotian’ commentary in which the great thinker had been shrouded, revealing a Pufendorf well-known in the 1680s—a formidable and dangerous natural jurist and political theorist—but doubly obscured in the 1980s and still today, by a philosophical history that flies too high to see him, and by a commentary literature that too often does not like what it sees. David Saunders’ remarkable translation carries Palladini’s argument into English with maximum fidelity.
Keywords: Pufendorf, Samuel, Freiherr von, : 1632-1694; Natural law